INTEGRATION OF LOCAL WISDOM VALUES IN AQIDAH AKHLAK LEARNING AT MTSN BABUL MUJAHIDIN, BAYAN, NORTH LOMBOK - Khoirunnisa Khoirunnisa; Ismail Fahri; Husarida Husarida; Eldo Delamontano (Sekolah Tinggi Agama Islam Al Hidayah, 2026)
This study aims to investigate the implementation of local wisdom values in Aqidah Akhlak learning at MTsN Babul Mujahidin, Bayan, North Lombok. Aqidah Akhlak learning plays an important role in shaping students’ religious and social character; however, it is often delivered in a general manner and is insufficiently adapted to students’ cultural backgrounds. This study employs a qualitative approach with a descriptive case study design. Data were collected through in-depth interviews, observations, and document analysis. The findings indicate that the integration of local wisdom values into Aqidah Akhlak learning contributes to improvements in students’ religious behavior and social attitudes. Students demonstrate higher discipline in performing congregational prayers, stronger awareness of mutual cooperation, and greater respect for teachers and peers. In addition, students from pesantren backgrounds exhibit more consistent religious practices compared to non-pesantren students. The implementation of local cultural practices, such as deliberation (musyawarah) and communal activities, helps students internalize moral values in a more contextual and meaningful way. This study concludes that integrating local wisdom into Islamic education can serve as an effective strategy for strengthening students’ character by connecting religious teachings with their socio-cultural environment